Concept of Education in Children Before Birth - Abdillah (Journal of Public Policy Analys, 2024)
Prenatal child education is a strategic approach that focuses on stimulating and developing a child's potential from the time they are in the womb. This concept is rooted in the belief that the prenatal period is a critical period for building a strong physical, emotional, and cognitive foundation. Through methods such as verbal communication, musical stimulation, and maintaining the mother's psychological condition, prenatal education aims to create an intrauterine environment that is conducive to optimal fetal growth. Research shows that these interactions can influence brain development, shape sensory preferences, and strengthen the emotional bond between parent and child. The prenatal education approach does not only involve biological aspects, but also psychological and spiritual. The mother's emotional state, such as stress levels and mood, has a significant impact on fetal development. Therefore, prenatal education includes stress management techniques, meditation, and spiritual activities to improve the mother's mental balance. Apart from that, the father's role is also important in creating a harmonious atmosphere in the family environment, providing emotional support, and actively participating in prenatal stimulation activities. Implementation of prenatal child education requires collaboration across disciplines, including medicine, psychology and education. In practice, this concept can be realized through educational programs for parents, which include prenatal communication skills training, nutritional guidance, and introduction to fetal development. With an integrated approach, prenatal education has the potential to improve the quality of future generations, while strengthening family relationships from the start of a child's life.